Calcium dobesilate Is protective against Inflammation and oxidative/nitrosative stress in the retina of a type 1 diabetic rat model - Voabil, Paula (2017)
Calcium dobesilate (CaD) has been prescribed to some patients in the early stages of diabetic retinopathy to delay its progression. We previously reported that the treatment of diabetic animals (4 weeks of diabetes) with CaD, during the last 10 days of diabetes, prevents blood-retinal barrier breakdown. Here, we aimed to investigate whether later treatment of diabetic rats with CaD would reverse inflammatory processes in the retina. Diabetes was induced with streptozotocin, and 6 weeks after diabetes onset, CaD (100 mg/kg/day) was administered for 2 weeks. The treatment with CaD significantly increased glial fibrillary acidic protein (GFAP) levels in the retina of nondiabetic animals (138.6 ± 12.8% of control) and enhanced the diabetes-induced increase in GFAP levels (174.8 ± 5.6% of control). In addition, CaD prevented the increase in mRNA and protein expression of tumor necrosis factor and interleukin-1β, as well as the formation of oxidized carbonyl residues and the increase in nitrotyrosine immunoreactivity, particularly in the ganglion cell layer of diabetic animals. We demonstrate that the treatment of diabetic animals with CaD can reverse the established proinflammatory processes in the retina. These beneficial effects appear to be attributed, at least partially, to the antioxidant properties of CaD.